Academic and psychological determinants of mental stress among medical students in Dhaka: A multinomial logistic regression approach - Maliha Khan Majlish; Mushfiqur Rahman Khan Majlish; Sabrin Shohid; Md Samiul Islam; A. N. M. Shamsul Islam (PLoS ONE, 2026)
As stress among medical students is a global health concern due to comprehensive academic engagements, this study aimed to assess the educational and psychological factors related to mental stress among medical students in Dhaka city. A descriptive type of cross-sectional study was conducted in two medical colleges in Dhaka city among 380 medical students from 3 rd year to 5 th year, using a pre-tested, self-administered, and structured questionnaire. The data obtained were analyzed using IBM SPSS Statistics (version 23) and Stata (version 14.2) employing the chi-square association test for bivariate analysis and subsequent multinomial logistic regression for the significant variables. Among 380 respondents, 68.7% were female, with 51.8% of respondents from Shaheed Suhrawardy Medical College. The mean stress score of medical students was 21.64 (SD = 6.64), with 67.9% and 22.6% as moderately and highly stressed, respectively. In bivariate analysis, 29 academic factors and 09 psychological factors were significantly associated with stress. In multinomial logistic regression analysis, three models were conducted, containing variables related to academic stress in model 1, variables related to psychological stress in model 2, and all stress variables in model 3. From model 1, academic performance, study and exam score anxiety, fear of future uncertainty and new living, administration satisfaction, and lack of entertainment facilities are significantly associated with stress. Additionally, the factors significantly associated with stress are time management, social life perception, and feeling lonely for model 2 and all stress-related variables, including study and exam score worry, difficulty in understanding context, fear of new living, administration and lecture satisfaction, teaching strategy satisfaction, time management, parental support in study, and feeling loneliness for model 3. Proper interventions for stressors of mental stress, further assessment, and rehabilitation for high and moderate-stressed respondents could be a prime concern to lessen the burden of stress among medical students.